The inverse electron demand Diels–Alder cycloaddition with carbon‐11 and fluorine‐18: A gateway to pretargeted imaging across the blood–brain barrier - Zientek, Simon H.; Thompson, Stephen; Sephton, Selena Milicevic; Aigbirhio, Franklin I. (Journal of labelled compounds & radiopharmaceuticals, 2023)
There is increased focus on developing tools to image large biomolecules, such as antibodies, within the brain using positron emission tomography (PET). The inverse electron demand Diels–Alder cycloaddition (IEDDA) reaction has offered the greatest prospect of achieving such a feat and has gained much interest over the past decade. The fast reaction kinetics of the IEDDA reaction opens up the possibility of utilising a pretargeted approach, whereby the subject is pretreated with a biomolecule that has high specificity for its target. A radiolabelled second component is then administered to the subject, enabling the biomolecule to be visualised by PET. However, for this to become common practice, there is a need for the development of either radiolabelled trans‐cyclooctenes (TCOs) or tetrazines that can cross the blood–brain barrier (BBB). This review highlights the advancements in the development of both radiolabelled TCOs and tetrazines, which have been radiolabelled with either carbon‐11 or fluorine‐18 and show promise or have been evaluated for use in pretargeted PET imaging across the BBB. There has been increased interest in the use of inverse electron demand Diels–Alder cycloaddition reaction in pretargeted PET imaging making use of tetrazines and trans‐cyclooctenes. This has opened up the possibility to perform pretargeted PET imaging within the brain. This review highlights the development of carbon‐11 and fluorine‐18 radiolabelled tetrazines and trans‐cyclooctenes and then explores their ability to cross the blood–brain barrier, their stability and finally their use in pretargeted PET imaging experiments.